Detection of human papillomavirus type 16 DNA in carcinomas of the palatine tonsil. Issue 11 (November 1990) - Niedobitek, G; Pitteroff, S; Herbst, H; Shepherd, P; Finn, T; Anagnostopoulos, I; Stein, H
Abstract : Twenty eight tonsillar carcinomas of various histological types were investigated for the presence of Epstein-Barr virus (EBV), cytomegalovirus (CMV), and human papillomavirus (HPV) types 6, 11, and 16 by in situ hybridisation using highly stringent procedures. In six cases an autoradiographic signal was obtained in the tumour cell nuclei with the HPV type 16 specific probe. No signal was obtained with any of the other probes. Immunohistochemical investigations with mouse monoclonal antibodies directed against the L1 protein of HPV type and a rabbit antiserum that detects common protein determinants of HPV gave negative results, thus indicating latent infection. Furthermore, a series of tonsils from controls with comparable age distribution was negative by both in situ hybridisation and immunohistology. These results indicate a possible role for HPV 16 in the aetiology of a proportion of tonsillar carcinomas.